Key Working for Families with Young Disabled Children - Bernie Carter; Megan Thomas (Hindawi Limited, 2011)
For families with a disabled child, the usual challenges of family life can be further complicated by the need to access a wide range of services provided by a plethora of professionals and agencies. Key working aims to support children and their families in navigating these complexities ensuring easy access to relevant, high quality, and coordinated care. The aim of this paper is to explore the key worker role in relation to "being a key worker" and "having a key worker". The data within this paper draw on a larger evaluation study of the Blackpool Early Support Pilot Programme. The qualitative study used an appreciative and narrative approach and utilised mixed methods (interviews, surveys and a nominal group workshop). Data were collected from 43 participants (parents, key workers, and other stakeholders). All stakeholders who had been involved with the service were invited to participate. In the paper we present and discuss the ways in which key working made a difference to the lives of children and their families. We also consider how key working transformed the perspectives of the key workers creating a deeper and richer understanding of family lives and the ways in which other disciplines and agencies worked. Key working contributed to the shift to a much more family-centred approach, and enhanced communication and information sharing between professionals and agencies improved. This resulted in families feeling more informed. Key workers acted in an entrepreneurial fashion, forging new relationships with families and between families and other stakeholders. Parents of young disabled children and their service providers benefited from key working. Much of the benefit accrued came from strong, relational, and social-professional networking which facilitated the embedding of new ways of working into everyday practice. Using an appreciative inquiry approach provided an effective and relevant way of engaging with parents, professionals, and other stakeholders to explore what was working well with key working within an Early Support Pilot Programme.